Practical justice as an innovative approach to addressing inequalities facing gender and sexually diverse people: a case example from Papua New Guinea. Issue 7 (2nd July 2020) - Kelly-Hanku, Angela; Aggleton, Peter; Boli-Neo, Ruthy
Abstract: Cultural values and practices influence many aspects of sexual and reproductive health and rights – from access to and quality of health education and services, to gender roles and responsibilities, to family planning and sexual freedoms. Culture is frequently marginalised in epidemiologically driven analyses of sexual and reproductive health and rights yet remains central to the ways in which inequalities within these fields manifest themselves and are engaged with in society. Using Papua New Guinea (PNG) as a case example, this paper sheds light on the enabling and restrictive role of culture in efforts to work towards equity and justice for gender and sexually diverse people. Drawing on four case stories, we offer insight into where culture can and has been deployed to redress serious inequalities in what is often a hostile environment. In these stories we illustrate how practical justice provides an innovative way to approach issues to do with sexual and reproductive health, particularly as they relate to enhancing the lives of people in visible, grassroots ways. In this way, given evidence, good normative judgement and the opportunity to do good and be fair, practical justice may be seen to be taking place.